Quasibilinear functionals - Fryda, Jan (Annales Mathematicae Silesianae, 1992)
In this paper a certain natural generalization of bilinear functional is introduced and investigated. We define quasibilinear functionals by replacing the additivity of a bilinear functional with three weaker conditions. The solution is a sequence of bilinear functionals on subspaces of the given linear space.